Analisis Rasio Kebutuhan Tenaga Dokter dengan Metode Work Sampling di IGD RSUD Malangbong Kabupaten Garut - Syafril Firdaus, Muhammad; Hadian Rahim, Agus; Veranita, Mira (ManBiz: Journal of Management and Business, 2025)
Doctors' services, especially in the Emergency Room, are very important for the lives and well-being of patients. The hospital provides emergency services continuously for 24 hours. The Emergency Room of Malangbong Regional Hospital, Garut is the leading unit in health services for the community. However, there is an imbalance between the number of general practitioners in the ER and the number of patients. The technique for calculating the number of general practitioners' human resources needs in this study can be based on the workload using ‘work sampling’. This study aims to determine the optimal number of general practitioners' human resources needs in the appropriate ER. Based on the results of the study, the types of direct productive activities by ER doctors are physical examinations, anamnesis and 'informed consent'. Meanwhile, indirect productive activities are filling in statuses, waiting for supporting examinations and waiting for patients. Based on the calculation of the need for doctors using the work sampling formula, the number of doctors needed in the ER of Malangbong Regional Hospital, Garut Regency is 15 people. The number of workers in the ER of Malangbong Regional Hospital were very lacking.